PENERAPAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIC RUQAYYAH SMP IT ABDURRAB PEKANBARU - Andri Andri; Armis Armis; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a classroom action research that aims to improve the learning process and increase the mathematics learning outcomes by applying the Learning Cycle 5E model. The subject of this research is students of class VIIC Ruqayyah SMP IT Abdurrab Pekanbaru on the second semester in the 2017/2018 academic years as many as 20 students, which all of whome are girls with heterogeneous levels of academic ability. The research consist of two cycles and each cycle has four stages, which are planning, implementation, observation, and reflection. The research instruments used are learning instruments (Syllabus, Lesson Plans, and Student Worksheet) and instruments for collecting data (Observation Sheets and Mathematical Learning Outcomes Tests). The observation sheets were used to find out the data of students and teacher activity during learning process which would analyzed qualitatively. Mathematics learning outcomes test were used to collect the student’s mathematical learning outcomes which would analyzed quantitatively. The analysis result of observation sheets indicated the learning process in cycle I were better than learning process in before action and learning process in cycle II were better than learning process in cycle I. The analysis result of the student’s mathematics learning outcomes scores indicated the percentage of students who reached Minimum Mastery Criteria (KKM) in base score is 40% increased to 70% in cycle I and 80% in cycle II. Based on the result above, it can be concluded that the implementation of Learning Cycle 5E model can improve the learning process and the mathematical learning outcomes of students class VIIC Ruqayyah SMP IT Abdurrab Pekanbaru on the second semester in the 2017/2018.Key Words: Learning Cycle 5E Model, Mathematics Learning Outcomes, Classroom ActionResearch